The INFLUENCE OF MARKETING CONTENT (SHORT VIDEOS) AND E-WOM ON TIKTOK ON THE PURCHASE INTENTION IN MAKARIZO HAIRCARE: A Study of TikTok Marketing Content and e-WOM on Makarizo Haircare Product - Siregar, Meirinda; Fatricia, Raja Sharah; Siregar, Ade Perdana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
The rapid growth of digital technology has transformed marketing strategies, particularly through social media platforms such as TikTok. Short-form video content and electronic word of mouth (E-WOM) have become important factors that influence consumer behavior and purchase interest. This study aims to analyze the influence of short video marketing content and electronic word of mouth (E-WOM) on TikTok on consumer purchase intention toward Makarizo haircare products. The research employed a quantitative approach with a causal-associative design. Data were collected through online questionnaires distributed via Google Form to 250 active TikTok users in Indonesia aged 18–34 years who had seen or recognized Makarizo marketing content. The sampling technique used was purposive sampling. Data were analyzed using SPSS through descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-test, F-test, and coefficient of determination (R²). The results show that short video marketing content has a positive and significant effect on purchase intention, with a regression coefficient of 0.810 and significance value of 0.000. Electronic word of mouth (E-WOM) also has a positive and significant effect on purchase intention, with a regression coefficient of 0.183 and significance value of 0.000. Simultaneously, marketing content and E-WOM significantly influence purchase intention, with an F-value of 1585.922 and significance value of 0.000. The coefficient of determination (R²) indicates that both variables explain 92.8% of the variation in purchase intention. These findings suggest that effective short video marketing strategies combined with credible electronic word of mouth can significantly enhance consumer purchase interest toward Makarizo haircare products.